Transformasi Pasar Kerja di Indonesia: Studi Kebijakan Ketenagakerjaan dalam UU Cipta Kerja - Rozikin, Irkham Syahrul; Muhyiddin, Muhyiddin (Journal of Social Movements, 2025)
Indonesia’s labor market has undergone significant dynamics due to economic transformation, digitalization, and the global pandemic. The Omnibus Law on Job Creation was designed to enhance labor market flexibility while attracting investment. However, this policy presents challenges in ensuring worker protection. This study examines policies related to Fixed-Term Employment Agreements (PKWT), outsourcing, wages, and severance pay using both qualitative and quantitative approaches. The findings indicate that although labor flexibility has increased, non-standard workers face risks of wage uncertainty and inadequate social security. The wage policy, which is based on a mathematical formula, provides predictability but does not fully protect informal sector workers. Severance pay reform is necessary to balance business sustainability with workers’ rights. This study recommends the separation of labor regulations, strengthening the protection of non-standard workers, and improving regulatory enforcement.